Effects of Mash Acidification - Reiter, Thomas; Back, Werner; Krottenthaler, Martin (BrewingScience, 2008)
Acidification can be useful not only for mash or wort, but also for the decarbonation of brewing liquor. According to the Provisional Beer Law in Germany, an acidification in the brewhouse is permitted, when the lactic acid is obtained biologically. This work gives an overview about the effects of mash acidification at different mashing-in temperatures. Laboratory trials were performed at 58-61-64 °C, on the one hand with and on the other hand without mash acidification (pH-lowering of 0.2 units). Industrial-scale tests, in which a total of over 19,000 hl wort was produced, showed that mash acidification up to a mashing-in temperature of 61 °C has a significant influence on the nitrogen content in wort. Formula for the calculation of the decarbonation are shown.